2001
DOI: 10.1143/jjap.40.l471
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Compensation with AlN Film on Y-128° LiNbO3

Abstract: Y-128° LiNbO3 is a well-known high-electromechanical-coupling Surface Acoustic Wave (SAW) material, but its usefulness is limited because of its poor temperature-stablility property. AlN films have some excellent characteristics, such as high SAW velocity, stable chemical properties, and high-temperature stability. In this research, the c-axis-oriented AlN films were successfully prepared on Y-128° LiNbO3 by the sputtering method and a SAW delay line oscillator under various temperatures was used to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Generally, AlN films can be synthesized using several techniques, such as reactive sputtering [4][5][6][7], molecular beam epitaxy [8], laser ablation [9], chemical vapor deposition (CVD) [10,11], and plasma-enhanced CVD [12]. Among these methods, the reactive magnetron sputtering technique is considered to be the favorable selection due to its easily deposited high c-axis orientation and its high growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, AlN films can be synthesized using several techniques, such as reactive sputtering [4][5][6][7], molecular beam epitaxy [8], laser ablation [9], chemical vapor deposition (CVD) [10,11], and plasma-enhanced CVD [12]. Among these methods, the reactive magnetron sputtering technique is considered to be the favorable selection due to its easily deposited high c-axis orientation and its high growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the minor loop size has a great effect on the magnetic stiffness. [22][23][24][25] The experimental results reported by Hull and Cansiz revealed that the average magnetic stiffness changed monotonically with the minor loop size. [22] We also simulated the average magnetic stiffness of various laterally or vertically sized minor loops changing from 0.1 mm to 2 mm when the PM moved vertically or horizontally above the HTS.…”
Section: Introductionmentioning
confidence: 90%
“…[22] We also simulated the average magnetic stiffness of various laterally or vertically sized minor loops changing from 0.1 mm to 2 mm when the PM moved vertically or horizontally above the HTS. [23][24][25] The calculation results demonstrated that most of the average magnetic stiffness values were intensely influenced by the sizes of the minor loops. In order to avoid the errors caused by different sizes of the minor loops, the approximate value of the magnetic stiffness was obtained using the linearly extrapolating to zero traverse method.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, depositing AlN films on 128°Y LiNbO 3 may provide a new piezoelectric material for SAW devices. Characteristics of sputtering AlN films on 128°Y LiNbO 3 were examined [7] and their SAW properties were measured [8,9]. Highly c-axis-oriented AlN films were achieved via the investigation of X-ray diffraction (XRD) [7].…”
Section: Introductionmentioning
confidence: 99%